Cu/Cu2O nanocrystals for electrocatalytic carbon dioxide reduction to multi-carbon products. Issue 17 (3rd February 2023) - Yang, Yisen; Tan, Zhonghao; Wang, Sha; Wang, Yanyue; Hu, Jingyang; Su, Zhuizhui; Zhao, Yingzhe; Tai, Jing; Zhang, Jianling
Abstract : Cu/Cu2 O nanocrystals were prepared for the efficient electrochemical conversion of carbon dioxide into multi-carbon products. Abstract : We demonstrate the electrochemical conversion of carbon dioxide into multi-carbon products catalyzed by Cu/Cu2 O nanocrystals, with a maximum C2+ faradaic efficiency of 75% in 0.10 M K2 SO4 aqueous solution at −2.0 V versus Ag/AgCl and a partial current density of 34 mA cm −2 .